The Role Of The Police In Combating Domestic Violence In The Karangasem Police Resort Jurisdiction - Putra, I Nyoman Suartha Adhi; Sihotang, Erikson; Suandika, I Nyoman (Jurnal Syntax Transformation, 2025)
Handling of domestic violence is handed over to the police as the spearhead of the investigation process and its handling is processed in accordance with applicable law. Police Efforts in Handling Domestic Violence in the Karangasem Police Jurisdiction, namely (1) Pre-Emptive Efforts (Non-Penal Facilities), are one of the non-penal efforts or outside the legal path that aims to foster society by trying to instill good norms or morals to eliminate the intentions of potential perpetrators of domestic violence. (2) Preventive Efforts (Non-Penal Facilities) are the last non-penal efforts that can be taken by the police to prevent domestic violence. Preventive efforts themselves are more towards efforts aimed at eliminating the opportunities that potential perpetrators have to commit a criminal crime. and (3) Repressive Efforts (Penal Facilities), are the last efforts that can be made by the police to overcome a criminal crime.